Persepsi Perawat Terhadap Fungsi Pengarahan Kepala Ruang tentang Kepatuhan dalam Menjalankan Hand Hygiene di Ruang Rawat Inap - Indiyani Indiyani; Mona Saparwati; Eko Susilo (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2020)
Patient’s safety is an effort from health workers in providing safe health services for patients. Hand hygiene is a general term that applies to wash hands with antiseptic and handrub antiseptic. The implementation of operational standards of handwashing compliance procedures requires directing function to the nurses from the head of room. The type of this research was descriptive correlation with cross sectional approach. The population was all implementing nurses at Inpatient Room of Ungaran General Hospital as many as 82 nurses. 82 samples were taken by total sampling. The collecting data tool used a questionnaire ofnurse’s perception of directing function of head of room and observation sheet on hand hygiene. The research results showed that most of the heads of room performed good directing function as many as 76 people (92.7%),most of the nurses were compliance in practicing patient safety: five moment hand hygiene as many as 78 people (95,1%). The result of statistical test using Fisher's Exact Test obtained p value of 0,001 (α = 0,05). There is a correlation between nurse’s perception of directing function of head of room with nurses’ compliance in practicing hand hygiene in Inpatient Room of Ungaran General Hospital.Nurses need to increase patient safety awareness and compliance hand hygiene to minimize the incidence of nosocomial infections.Key words: directing function of head of roomnurses’ compliancehand hygienenurse’s perception